2022
DOI: 10.1007/s00520-021-06787-5
|View full text |Cite
|
Sign up to set email alerts
|

Routine cancer treatments and their impact on physical function, symptoms of cancer-related fatigue, anxiety, and depression

Abstract: Background and purpose Breast cancer can be a major challenge for affected women. Knowledge of the physical function, symptoms of cancer-related fatigue, anxiety, and depression based on the cancer treatment may help to guide adequate support. Methods For this prospective observational study, we collected data from seventy-nine women with a mean age 54.6 ± 9.5 years prior to the onset of breast cancer treatment (T0) and after (T1/T2). Handgrip strength te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Finally, it is worth noting that few medical variables emerged as significant predictors of the M12 overall mental health change. These included specific symptoms related to BC treatments 10 , 11 , indices of immune response, and relatively higher thrombocyte count 12 , 13 . The role of BC treatments or subsequent mental and functional well-being has been highlighted by recent studies 10 , 11 however in our study treatments were not among the strong predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth noting that few medical variables emerged as significant predictors of the M12 overall mental health change. These included specific symptoms related to BC treatments 10 , 11 , indices of immune response, and relatively higher thrombocyte count 12 , 13 . The role of BC treatments or subsequent mental and functional well-being has been highlighted by recent studies 10 , 11 however in our study treatments were not among the strong predictors.…”
Section: Discussionmentioning
confidence: 99%
“…These included specific symptoms related to BC treatments 10 , 11 , indices of immune response, and relatively higher thrombocyte count 12 , 13 . The role of BC treatments or subsequent mental and functional well-being has been highlighted by recent studies 10 , 11 however in our study treatments were not among the strong predictors. At present we may only surmise on the mechanisms responsible for the impact of biological measures.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of fatigue is closely related to the growth of cancer cells and decreases in the inflammatory factors and in the hemoglobin level of the body itself. [28][29][30][31] This study explored the mechanism of a physical therapy on fatigue and cellular immunity. TEAS intervention can facilitate the release of endorphins and enkephalins from the brain to regulate the nervous, endocrine, and immune systems 11,32 bidirectionally.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that compared with the AM Group and the FAM Group, the SI-TEAS Group had the greatest changes in fatigue and immunity after 4 and 8 weeks of intervention, which confirmed significant intervention effects; in contrast, although the AM Group experienced similar relief in their fatigue symptom, their overall improvement was lower than that of the SI-TEAS Group; the application of sham acupressure had no clinical efficacy on the fatigue and immunity of the CRF patients. The occurrence of fatigue is closely related to the growth of cancer cells and decreases in the inflammatory factors and in the hemoglobin level of the body itself 28–31. This study explored the mechanism of a physical therapy on fatigue and cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A patient's physical and cognitive function are important for treatment decision making and treatment tolerability [23,24], and therefore understanding the relationship between the two may assist clinicians in designing individualized treatment plans for older adults with cancer. Assessment of cognition and physical function prior to treatment are also important given that both are profoundly impacted by cancer treatment [25,26]. The objective of this study was to examine the associations between objective measures of physical function and cognitive impairment in older adults with cancer who had undergone GA prior to treatment.…”
Section: Introductionmentioning
confidence: 99%